Acropetal Auxin Transport Inhibition Is Involved in Indeterminate But Not Determinate Nodule Formation - Ng, Jason L. P.; Mathesius, Ulrike (Frontiers in Plant Science, 2018)
Legumes enter into a symbiotic relationship with nitrogen-fixing rhizobia, leading to nodule development. Two main types of nodules have been widely studied, indeterminate and determinate, which differ in the location of the first cell division in the root cortex, and persistency of the nodule meristem. Here we compared the control of auxin transport, content and response during the early stages of indeterminate and determinate nodule development in the model legumes Medicago truncatula and Lotus japonicus, respectively, to investigate whether differences in auxin transport control could explain the differences in the location of cortical cell divisions. While auxin responses were activated in dividing cortical cells during nodulation of both nodule types, auxin (indole-3-acetic acid) content at the nodule initiation site was transiently increased in M. truncatula, but transiently reduced in L. japonicus. Root acropetal auxin transport was reduced in M. truncatula at the very start of nodule initiation, in contrast to a prolonged increase in acropetal auxin transport in L. japonicus. The auxin transport inhibitors 2,3,5-triiodobenzoic acid (TIBA) and 1-N-naphtylphthalamic acid (NPA) only induced pseudonodules in legume species forming indeterminate nodules, but failed to elicit such structures in a range of species forming determinate nodules. The development of these pseudonodules in M. truncatula exhibited increased auxin responses in a small primordium formed from the pericycle, endodermis and inner cortex, similar to rhizobia-induced nodule primordia. In contrast, a diffuse cortical auxin response and no associated cortical cell divisions were found in L. japonicus. Collectively, we hypothesise that a step of acropetal auxin transport inhibition is unique to the process of indeterminate nodule development, leading to auxin responses in pericycle, endodermis and inner cortex cells, while increased auxin responses in outer cortex cells likely require a different mechanism during the formation of determinate nodules.